2015
DOI: 10.3892/ol.2015.3574
|View full text |Cite
|
Sign up to set email alerts
|

Complete regression of adult pineoblastoma following radiotherapy: A case report and review of the literature

Abstract: Abstract. Adult pineoblastomas (PBs) are rare central nervous system tumors. Little is known with regard to the clinical features and outcomes of adult PB, and optimal treatment strategies for adult PB remain to be determined. The current report describes a case of PB in a 46-year-old male, who presented with obstructive hydrocephalus due to a large pineal region mass. Considering the potential effect on quality of life, the patient underwent a partial resection. Postoperative radiotherapy, comprising prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…6,8 Previous studies showed that heterogeneous enhancement is common in PBs. 4,9 Our study also confirmed this observation and found that hypo-intense on T1 weighted images and hyper-intense on T2 weighted images occurred mainly for the radiologic features.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…6,8 Previous studies showed that heterogeneous enhancement is common in PBs. 4,9 Our study also confirmed this observation and found that hypo-intense on T1 weighted images and hyper-intense on T2 weighted images occurred mainly for the radiologic features.…”
Section: Discussionsupporting
confidence: 86%
“…While the administration of adjuvant radiotherapy for PBs in adults has been identified to be useful to increase OS, a statistically significant effect on OS was not demonstrated owing to limited case reports. 6 , 9 , 12 One case report advocated adjuvant chemotherapy for adult patients. 15 In a previous large series of 34 adult cases, the contribution of chemotherapy to a favorable OS remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2701 articles retrieved in the search, 44 studies with IPD on 298 patients with pineoblastoma were included in the systematic review ( Table 1 ) [ 5 , 6 , 8 , 9 , 10 , 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Figure 1 presents the PRISMA flowchart for this systematic review [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, starting from the second decade, adult cases are very rare and represent less than 10% of published literature (6). For this reason, limited data are currently available in the effort of developing a standard management of the disease, with a lack of consensus about the optimal combination of a multimodality treatment involving surgery, radiotherapy and/or chemotherapy.…”
mentioning
confidence: 99%